Faktor-Faktor yang Memengaruhi Ketidakpatuhan Pasien Thalassemia dalam Mengonsumsi Obat Kelasi Besi di RSUD Al Ihsan Bandung 2023 - Ridwan Maulana Assidiq; Agung Firmansyah Sumantri; Ayu Prasetia (Bandung Conference Series: Medical Science, 2024)
Abstract. Thalassemia is a hereditary disease that causes disturbance in hemoglobin molecules. Currently, a curative treatment that is accessible to people is blood transfusion. To treat side effects that may arise. Thalassemia patients are given iron-chelating agents to treat excess iron in the body. However, patients often lack compliance with treatment. So, this study aims to identify factors influencing thalassemia patients’ non-compliance in taking iron chelating agents at Al Ihsan Hospital, Bandung 2023. This study was a cross-sectional study conducted at Al Ihsan Hospital, Bandung on 46 patients. Data were obtained by filling out the questionnaire to identify factors influencing thalassemia patients’ non-compliance with taking iron-chelating agents, analyzed with univariate. This study was divided into two groups based on age, child and adult. Both ages group was dominated by patients who had low compliance rates, the child with 18 patients (75%) and adult also with 18 patients (81.8%). After the analysis was carried out, it was found that belief, ferritin level, number of drugs, busyness, drug administration, social stigma, economic, and adverse effects of drug factors could influence thalassemia patients’ non-compliance in taking iron chelating agents. The majority of adult patients are caused by number of drugs factor (68.2%) and the majority of children patients are caused by number of drugs and drug administration factors (50%). Patients at Al Ihsan Hospital Bandung 2023 found that the majority of adult patients are caused by number of drugs factor while the majority of children patients are caused by number of drugs and drug administration factors. Abstrak. Thalassemia merupakan penyakit herediter yang menyebabkan gangguan pada molekul hemoglobin. Pengobatan kuratif yang dapat diakses masyarakat saat ini adalah transfusi darah. Untuk menangani efek samping yang mungkin timbul. pasien Thalassemia diberikan agen kelasi besi untuk mengatasi berlebihnya zat besi dalam tubuh. Namun, seringkali pasien kurang patuh dalam pengobatan. Sehingga penelitian ini bertujuan untuk mencari faktor-faktor yang memengaruhi ketidakpatuhan pasien thalassemia dalam mengonsumsi obat kelasi besi di RSUD Al Ihsan Bandung 2023. Penelitian ini merupakan penelitian cross-sectional yang dilakukan di RSUD Al Ihsan Bandung pada 46 pasien. Data diperoleh dari pengisian kuesioner untuk mencari faktor yang memengaruhi ketidakpatuhan pasien thalassemia dalam mengonsumsi obat kelasi besi dan dianalisis dengan uji univariat. Data penelitian ini dibagi menjadi dua kelompok berdasarkan usia, yaitu anak dan dewasa. Kedua kelompok usia didominasi oleh pasien yang memiliki tingkat kepatuhan rendah, pada usia anak terdapat 18 pasien (75%) dan usia dewasa 18 pasien (81.8%). Setelah dilakukan analisis ditemukan bahwa faktor kepercayaan, kadar ferritin, jumlah obat, kesibukan, administrasi obat, stigma sosial, ekonomi, dan efek samping dapat memengaruhi ketidakpatuhan terhadap konsumsi kelasi besi. Pada mayoritas pasien dewasa disebabkan oleh faktor jumlah obat (68.2%) dan mayoritas pasien anak disebabkan oleh faktor jumlah obat juga administrasi obat (50%). Pasien di RSUD Al Ihsan Bandung 2023 ditemukan mayoritas pasien dewasa disebabkan oleh faktor jumlah obat sedangkan mayoritas pasien anak disebabkan oleh faktor jumlah obat dan administrasi obat.